Understanding the share ownership of institutional investors in Malaysia - Abd Mutalib, Hafizah; Muhammad Jamil, Che Zuriana; Wan Hussin, Wan Nordin (INSInet Publications, 2016)
The vast amount of assets owned by institutional investors has significantly altered the ownership structure of organizations.The purpose of this study is to explore the share ownership by institutional investors among firms listed on Bursa Malaysia.The sample consists of 330 firms as listed in 2011, and the share ownership of institutional investors is measured by the percentage of ownership held by the institutional investors in the annual report.The results reveal that more than two-third of the firms under study has share ownership by institutional investors. The largest share ownership is by the unit trusts and mutual funds institutions.Furthermore, by separate institutions, the government-managed unit trust fund, namely the Permodalan Nasional Berhad (PNB) and the ‘Pilgrims Fund’ or the Lembaga Tabung Haji (LTH) hold the highest percentage of share ownership, followed by the government-managed pension fund, namely the Employees Provident Fund (EPF).When institutions are classified according to their investment behavior, dedicated institutions mark a higher level of ownership compared to transient institutions. Moreover, government-managed institutions significantly dominate the market for institutional shareholdings.